Digital transformation in administrative mail management: Evaluating NADIA’s impact on accuracy, speed, and compliance - Ni Kadek Sinta Septiadana; I Made Widiantara; Ni Luh Eka Armoni; Majid Wajdi; Augustine Etim Effiong (Yayasan Mitra Persada Nusantara, 2025)
This study aims to examine the procedure for managing incoming letters using the NADIA (Naskah Dinas InJourney Airports) application at PTAPI. The implementation of the NADIA application represents a shift from conventional manual correspondence to a more integrated, digital-based document management system. The objective of this research is to describe and evaluate the effectiveness, efficiency, and challenges of managing incoming correspondence through the NADIA system. A qualitative descriptive method was employed, using data collection techniques such as observation, interviews with key administrative personnel, and documentation review of incoming letters and related correspondence procedures. The analysis focused on stages of the incoming mail process, which include document receipt, classification, digital distribution, and archiving, all facilitated by the NADIA system. Findings show that the NADIA application has significantly improved the traceability, accuracy, and timeliness of handling incoming letters. It allows better monitoring, reduces document loss, and promotes environmentally friendly practices by minimizing paper use. However, several challenges were identified, such as limited training for users, occasional technical issues, and adaptation barriers among senior staff. The study concludes that while the NADIA application enhances administrative efficiency, its effectiveness depends largely on adequate socialization, infrastructure readiness, and continuous technical support. It is recommended that PTAPI improve training and provide user support to optimize the application’s potential and ensure consistent use across departments